2016
DOI: 10.1038/srep38584
|View full text |Cite
|
Sign up to set email alerts
|

Latent curing systems stabilized by reaction equilibrium in homogeneous mixtures of benzoxazine and amine

Abstract: Latent curing systems are widely used in industrial thermosets in applications such as adhesion, coating, and composites. Despite many attempts to improve the practicality of this dormant reaction system, the majority of commercially available latent products still use particulate hardeners or liquid compounds with blocked active groups. These formulations generally lack fluidity or rapid reaction characteristics and thus are problematic in some industry applications. Here we describe a novel concept that stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Figure 2 shows the FT-IR spectra of PBZ-SA2 thermoset compared with pure PBZ and BZ monomer. The oxazine ring of BF showed three characteristic peaks at 934 cm −1 , 1026 cm −1 , and 1223 cm −1 , assigned to the ring symmetric and anti-symmetric stretching of the C-O-C bond 29 31 . However, the three peaks in PBZ were almost disappeared completely, and characteristic peaks assigned to tetra-substituted benzene (1450–1480 cm −1 ) increased 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the FT-IR spectra of PBZ-SA2 thermoset compared with pure PBZ and BZ monomer. The oxazine ring of BF showed three characteristic peaks at 934 cm −1 , 1026 cm −1 , and 1223 cm −1 , assigned to the ring symmetric and anti-symmetric stretching of the C-O-C bond 29 31 . However, the three peaks in PBZ were almost disappeared completely, and characteristic peaks assigned to tetra-substituted benzene (1450–1480 cm −1 ) increased 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Benzoxazine resin is a novel kind of high performance thermosetting resin [9][10][11]. Due to high glass transition, nearly zero volume shrinkage and no volatile release during the curing processes, good flame resistance and good thermal stability, their fiber reinforced composite laminates were intensively studied and widely used [12][13][14][15]. As previous researches [16] indicated that the ring-formation reaction of the nitrile groups can be catalyzed by hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in the development of latent polymerization initiators that are inert in monomers or prepolymers under storage conditions. Latent thermal initiators must retain high activity under targeted temperatures while maintaining stability under storage conditions [1][2][3][4][5][6][7][8][9][10]. We have previously reported that primary alkylamines intercalated with α-zirconium phosphate (α-ZrP) can serve as latent thermal initiators in the reaction of glycidyl phenyl ether (GPE) [11,12] and that intercalation compounds of 1,4-diazabicyclo [2,2,2]octane (DABCO), 1,8-diazabicyclo [5,4,0]undec-7-ene (DBU), imidazole (Im), 2-methylimidazole (2MIm), and 2-ethyl-4-methylimidazole (2E4MIm) with α-ZrP (α-ZrP•DABCO, α-ZrP•DBU, α-ZrP•Im, α-ZrP•2MIm, and α-ZrP•2E4MIm, respectively) show good performance as latent thermal initiators in the reaction of GPE with hexahydro-4-methylphthalic anhydride (MHHPA) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%